2018
DOI: 10.1111/teth.12417
|View full text |Cite
|
Sign up to set email alerts
|

Lost in the great divide: Motivation in religious studies classrooms

Abstract: One of the most illuminating finds in Barbara E. Walvoord's Teaching and Learning in College Introductory Religion Courses (2008) is what she calls "the great divide," a mismatch between instructors' goals for their courses, which are academic, and the students' reasons for taking them, which relate to their personal interests and development. Motivation -or, rather, the lack thereof -is not explicitly considered as a potential victim of this mismatch. This article will turn its attention squarely to this iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, what I have observed across the board, is that students struggle with personal narratives, particularly with personal stories of suffering or abuse. In a recent Teaching Theology and Religion article, Emily Gravett () offers a helpful summary of the ways in which, particularly in religion courses, we often teach students to bracket their personal narratives and values in order to critically engage class materials. I argue that bracketing the personal is part of the larger epistemological ethos of universities and even of theological education.…”
Section: Difficulty With Personal Narratives and Emotionsmentioning
confidence: 99%
“…However, what I have observed across the board, is that students struggle with personal narratives, particularly with personal stories of suffering or abuse. In a recent Teaching Theology and Religion article, Emily Gravett () offers a helpful summary of the ways in which, particularly in religion courses, we often teach students to bracket their personal narratives and values in order to critically engage class materials. I argue that bracketing the personal is part of the larger epistemological ethos of universities and even of theological education.…”
Section: Difficulty With Personal Narratives and Emotionsmentioning
confidence: 99%
“…The images proved to be extremely helpful for encouraging our students to develop and apply their understanding of the religious studies concept of “myth” to their local everyday experiences in the city of Baltimore. One student reported that “the artwork itself is beautiful and makes me want to explore religion and the city more.” Another wrote: “I think the discussion is inspiring because we're looking at the real world and seeing religious values in it.” Research by Barbara E. Walvoord, Emily O. Gravett, and others demonstrates that motivation is a pivotal factor in student learning and that a “great divide” between instructor and student goals can lead to a lack of motivation (Walvoord, ; Gravett, ; Sabri et al, 2008). Though Walvoord's and Gravett's work focuses on the mismatch between the academic goals of instructors and students goals related to personal development (of their beliefs and commitments), we have found that many of our students' motivation to learn is also increased through an application of theory to local arts and issues.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Barbara E. Walvoord, Emily O. Gravett, and others demonstrates that motivation is a pivotal factor in student learning and that a "great divide" between instructor and student goals can lead to a lack of motivation (Walvoord, 2008;Gravett, 2018;Sabri et al, 2008). Though Walvoord's and Gravett's work focuses on the mismatch between the academic goals of instructors and students goals related to personal development (of their beliefs and commitments), we have found that many of our students' motivation to learn is also increased through an application of theory to local arts and issues.…”
Section: Introductionmentioning
confidence: 99%